Rancang Bangun Sistem Informasi Geografis Menemukan Lokasi Dokter Hewan Berbasis Android - Sularno Sularno; Nori Sahrun (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Geographic information systems (GIS) have the ability to connect various data at certain points on earth, combine, analyze, and finally map the results. Data will be processed in GIS spatial data which is geographically and location oriented data that has a certain coordinate system, as a basic reference. So the GIS application can answer several questions such as; location, conditions, trends, patterns and modeling. This capability distinguishes GIS from other information systems. By building a geographical information system it is hoped that it can help the public to find out where the location of veterinarians in the city of Padang is based on Android. So that people can more easily find the location of veterinarians in the city of Padang quickly and accurately that can be accessed via cell phones (Smartphones). In this geographic information system making additional application programs used are MapInfo, Android Studio, and other supporting applications.